Distribution of Shear Stress in the Meanders of Tigris River Within Baghdad City - Nama, Ala Hassan (Nahrain University College of Engineering Journal, 2015)
Distribution of bed and banks shear stress was studied considering the effect of bends on this distribution within the main three meanders, Al-Kadimiyah, Al-Atafiyah and Al-Jadiriyah in Tigris River within Baghdad City. A steady flow hydraulic model, using the HEC-RAS software, was used to simulate the flow in Tigris River within Baghdad City in order to obtain the flow characteristics in ten slices across the considered cross section along the river reach for the cases of 400, 800 and 1300 m3/s which represent the minimum, average and maximum discharge of the river flow during the period from 2000 to 2010.The calibration and verification process was carried out using two sets of discharge and stage measurements. These processes showed that the Manning’s n values were between 0.025 to 0.028 for the main channel and 0.038 to 0.042 for the left and right banks and the water surface slope was 7 cm/km.Application of the hydraulic model for the three cases of discharge (400, 800 and 1300 m3/s ) shows that the maximum and minimum flow velocity were (0.39, 1.11), (0.53, 1.13) and (0.57 and 1.37m/sec), respectively. While the water surface slopes varied from 6.5 to 8.5 cm/km for discharges between 400 and 1300 m3/s, respectively. These slopes increased at the bridges to about 9 cm/km.Results of applying the hydraulic model were used to compute the shear stress in each slice across all the considered cross sections for the three meanders using the reach-averaged boundary shear stress equation and the Federal Highway Administration guidance was used to estimate the shear stress within the high shear stress locations. The Arc-GIS software was used to process the data by making use of the available interference facilities between the HEC-RAS and Arc-GIS softwares.The estimated maximum shear stresses in the three bends for the discharges 400, 800 and 1300 m3/s showed that the meandering effect increase the maximum shear stress in Al-Kadimiyah, Al-Atafiyah and Al-Jadiriyah bends by about 16%, 22% and 31%, respectively.The locations and distribution of shear stress in the case of considering the meanders effect at the upstream and downstream of the bends does not affect. While it is changed in the bend and become coincident with the characteristics of flow and river geometry. The influence of disparity in the values of shear stress appears through upgrowth of the islands within the river at the locations of low shear stress with continuous changes in the geometry of the river to be coincident with the distribution of shear stress.